Penguatan Kreativitas Visual dan Pemahaman Perspektif Arsitektur Melalui Lomba Sketsa Manual Bagi Siswa SMA - Firnawati Firnawati; Jusbaeni Jusbaeni; Nahridzah Mahjubuh Shiber; Muh. Aryanugraha Ismajaya; Andi Firman Muhibuddin (ABDIMASY: Jurnal Pengabdian Kepada Masyarakat, 2026)
This community service activity in the form of an architectural sketch competition among high school students was motivated by the declining interest in manual drawing skills and the limited understanding of basic architectural concepts, particularly perspective and visual representation. The activity aimed to enhance students’ visual creativity, observational skills, and spatial understanding through a hands-on learning approach. The method employed was experiential learning through a live sketch (on-the-spot) activity, where participants were required to draw the Menara Phinisi Building of Universitas Negeri Makassar using manual (freehand) techniques. The implementation stages included preparation, competition execution, technical guidance, and evaluation by a panel of judges. The results showed that all participants were able to produce sketch works demonstrating a fairly good application of perspective principles, as well as diverse visual styles reflecting their creativity. The activity also improved students’ visual thinking skills, accuracy, and active engagement throughout the process. The impact of this activity includes increased understanding of architectural concepts and growing interest in the field of art and design. It is recommended that similar activities be developed sustainably as an effective practice-based educational medium for young learners.